cKIT Mutations in GISTs and Other Malignancies in Thailand - Prempree, Thongbliew; Wongpaksa, Chalorboon (Siriraj Medical Journal, 2006)
Objective: 1) To further identify tumors other than GISTs; 2) To study cKIT gene mutation for proper Imatinib treatment. Methods: Fresh tumor tissue samples were obtained from: 2 tissue samples of GISTs; 1 parotid cancer; 1 soft tissue sarcoma; 1 chondrosarcoma; 1 liposarcoma and 1 pure seminoma. The fresh tissues were divided into two portions: one for histopathological diagnosis and cKIT protein study, the other for DNA extraction and cKIT gene mutation study. Results: The authors described the gastrointestinal stromal tumors (GISTs) and other malignancies associated with positive cKIT protein in Thailand. We also describe briefly the methodology and molecular techniques used in the study of the mutation of cKIT gene in our laboratory using DNA sequencing method. Examples of positive cKIT protein and deletion mutation as well as missense (point mutation) mutations from our own patients are shown. Mutation study of exons 9, 11, 13 and 17 of cKIT gene in all 7 patients was carefully done to assist us in treating those patients with Imatinib therapy. Conclusion: Mutation study of cKIT gene could be done routinely in our molecular laboratory in Thailand. We recommend cKIT gene mutation study be done in every case of GIST and tumor with positive cKIT protein other than GIST prior to initiation of Imatinib therapy.